Quality of Life of Children with Learning Disabilities: A Comparison of Self‐Reports and Proxy Reports. Issue 3 (August 2015) - Sakız, Halis; Sart, Zeynep Hande; Börkan, Bengü; Korkmaz, Barış; Babür, Nalan
<x xml:space="preserve">Abstract</x> This study aimed to explore how children with learning disabilities (LD) perceive their quality of life (QoL) and to compare self‐reports and proxy reports regarding their QoL. Children with LD, their typically developing peers, their parents and teachers responded to the child, parent, and teacher forms of KINDLR Questionnaire for Measuring Health‐Related Quality of Life (Ravens‐Sieberer & Bullinger, 1998). Findings showed that children with LD reported significantly lower QoL scores than those reported by typically developing peers. Intraclass correlation coefficients (ICCs) and t‐test results showed that agreement between child reports and parent‐proxy reports was either low or moderate on each QoL dimension. Findings of the study may be used to raise awareness regarding the social and educational needs of children with LD in Turkey.